2018
DOI: 10.4103/jfmpc.jfmpc_248_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and anxiety among children in rural and suburban areas of Eastern Uttar Pradesh: A cross-sectional study

Abstract: Background:Psychiatric morbidity in children and adolescents is a major concern as they become more complex and intense with children's transition into adolescence.Aim:The aim of this study is to assess and compare the prevalence of depression and anxiety among children residing in rural and suburban area of eastern Uttar Pradesh and understand the burden of these problems in our society.Materials and Methods:Children, in the age group 11–18 years, were divided into 2 groups: Group I – 100 children from rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
10
19
1
1
Order By: Relevance
“…18 Other studies in Nepal state that 12.9-30% of adolescents had psychosocial problems. 5,19,20 In our findings anxiety disorders were found to be the commonest, this is similar to the meta-analysis done by Polanczyk,et al 6.5%, 21 on the worldwide prevalence of mental disorders in children and adolescents, similar findings were recorded by Pillai, et al 1%, 10 Roberts 6.9%, 22 Mishra 15%, 23 Kessler, et al 24 In a study done in Dang district, (46.5%) of the secondary school adolescents had anxiety. 25 Our study showed mood disorder to be the second most common disorder.…”
Section: Discussionsupporting
confidence: 92%
“…18 Other studies in Nepal state that 12.9-30% of adolescents had psychosocial problems. 5,19,20 In our findings anxiety disorders were found to be the commonest, this is similar to the meta-analysis done by Polanczyk,et al 6.5%, 21 on the worldwide prevalence of mental disorders in children and adolescents, similar findings were recorded by Pillai, et al 1%, 10 Roberts 6.9%, 22 Mishra 15%, 23 Kessler, et al 24 In a study done in Dang district, (46.5%) of the secondary school adolescents had anxiety. 25 Our study showed mood disorder to be the second most common disorder.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of anxiety disorders among adolescents in the current study (22.7%) was higher than that observed in a study done in Uttar Pradesh. [11] Unlike our study, the later used Revised Children's Manifest Anxiety Scale (RCMAS) to estimate the prevalence of anxiety disorders among adolescents. SCARED tool, a modern instrument than RCMAS, is more closely connected to DSM and more precise in diagnosing anxiety problems in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…There are many community-based studies that evaluated the point prevalence of depression or psychiatric disorders in different age groups. [38394041424344454647484950515253545556] However, there are a limited number of studies that specifically focused on children and adolescents. [3839404142434445] Most studies focused on any age group and included children and adolescents too in the process and did not provide specific point prevalence data for depression in children and adolescents.…”
Section: Epidemiology Of Depression In Children and Adolescentsmentioning
confidence: 99%
“…[38394041424344454647484950515253545556] However, there are a limited number of studies that specifically focused on children and adolescents. [3839404142434445] Most studies focused on any age group and included children and adolescents too in the process and did not provide specific point prevalence data for depression in children and adolescents. [4647484950515253545556] Nandi et al provided data on point prevalence of psychiatric disorders in a rural population from West Bengal and reported lack of depression in children and adolescents.…”
Section: Epidemiology Of Depression In Children and Adolescentsmentioning
confidence: 99%